OPTIMASI, KARAKTERISASI, SERTA UJI AKTIVITAS ANTIOKSIDAN NANOPARTIKEL PERAK HASIL SINTESIS MENGGUNAKAN EKSTRAK KULIT PETAI (PARKIA SPECIOSA) SEBAGAI BIOREDUKTOR - Pangestuti, Novi
Petai (Parkia speciosa) is one of the typical plants that grows in Indonesia and can be used as a source of antioxidants. In this study, petai peels was used as a bioreductant in the green synthesis of silver nanoparticles. Petai peels that has been chopped and dried then macerated in water for 2 hours. The filtered extract solution was reacted with AgNO3 solution and stirred while reacting. The mixture was then microwaved and incubated for 15 minutes. In the synthesis of nanoparticles, optimization was carried out under various conditions, such as variations in AgNO3 concentration, extract concentration, ratio of AgNO3 solution and extract, microwave power and time, and variations in pH. The formed nanoparticles were then characterized using UV-Vis spectrophotometry, Particle Size Analyzer (PSA), Fourier Transform Infrared Spectroscopy (FTIR), Transmission Electron Microscopy (TEM). From the test results, it was found that the optimal conditions for the synthesis of silver nanoparticles were AgNO3 concentration of 7 mM, extract concentration of 7%, ratio 1:1 (v/v), 200 Watt microwave power with 120 seconds and alkaline conditions pH 9. Nanoparticle characterization results showed that the nanoparticles formed were spherical or spheric, with an average size of 58.6 nm with a PI of 0.280. The IC50 from antioxidant activity test, IC50 of vitamin C, AgNO3, extract and silver nanoparticles is 13.92 µg/mL; 55.246 µg/mL; 38.9807 µg/mL; dan 47.728 µg/mL.